Penerapan Desain Produk Purple Goods dengan Pendekatan Strategi Diferensiasi - Callista, Jesslyn; Aryani, Dewi Isma (Fakultas Desain Universitas Komputer Indonesia, 2023)
Product design is indispensable for innovation and promotion in a brand. Differentiation strategy is a strategy within a company or business in order to survive in the midst of business competition, with the inovation of new product in accordance to fullfil customers needs. These two things are related to the continuity of a business, a business should have something different from its competitors to ensure the convenience of products entering the market and increase brand awareness among the public. By differentiating its products and designs, a business can highlight its brand image by applying brand characteristics to their product designs. With an attractive product design, out of the box, and different from other brands, it will be easier to attract customers' attention and can be a certain value to determine the characteristics of a brand so that it can be patented by customers. Not only product design, the quality of a product also guarantees consumer decisions and perceptions in choosing a product.